Transmission Easement and Adverse Possession of Transmission Easement in the Polish Law - Rosicki, Remigiusz (Wyższa Szkoła Bezpieczeństwa, 2016)
The object of analysis in the text are the issues concerned with the transmission easement and the adverse possession thereof on the grounds of the Polish civil law. The main sections of this thesis address the following issues; (1) a historical outline of the solutions concerned with easements in the Polish law following 1945, (2) the institution of transmission easement introduced in 2008 and the solutions concerned with the claims for the establishment thereof at court, (3) the institution of adverse possession of transmission easement pursuant to civil law regulations, judicature and the legal doctrine. With a view to elaborating the research issues, the thesis addresses the following research questions: (1) What function is performed by the institution of transmission easement in the system of civil-law relations in the Polish law?, (2) What legal problems in the civil-law relations does the application of the institution of transmission easement by adverse possession entail?
The object of analysis in the text are the issues concerned with the transmission easement and the adverse possession thereof on the grounds of the Polish law. The text features: (1) a historical outline of the solutions concerned with easements in the Polish law following 1945, (2) the institution of transmission easement introduced in 2008 and the solutions concerned with the claims for the establishment thereof at court, (3) the institution of adverse possession of transmission easement pursuant to civil law regulations, judicature and the legal doctrine. On account of the need to elaborate the wide-ranging legal issues concerned with the transmission easement in this text, the analysis embraces two research questions giving rise to the following conclusions: (1) What function is performed by the institution of transmission easement in the system of civil-law relations in the Polish law? The legislator in the articles introducing a transmission easement ossified the solutions functioning in the judicature of the Polish courts before 2008. The legal interpretation took a turn for clarification, that is for the establishment of a norm in the situation where its comprehension was dubious. It is noteworthy that in the period prior to 2008, the law provided for easement appurtenant, and on account of the usual course of judicial decisions also for easement appurtenant with the content corresponding to transmission easement. In 2008 these two “legal existences” were supplemented with a transmission easement, which nevertheless failed to resolve all the legal problems; nay, this gave rise to even more problems, e.g. the one of non-establishment of interpolar norms which would address the issues arising in connection with the use of various easement institutions in legal transactions. While amending the civil law, the legislator aimed to bring order to legal transactions by streamlining the unregulated actual state of easement in relation to transmission infrastructure, but also in relation to the situations where an easement was yet to be established and a facility yet to be constructed. Thus, such action is intended to regulate the disorderly legislation in force as well as to safeguard investment processes. This is of particular significance, for example, for energy companies which are burdened with statutory public-law obligations as regards securing energy supplies and providing for the development of energy infrastructure. Hence, the de facto introduced civil-law solutions indirectly served to realise the principles of the doctrine of easement in the public interest. (2) What legal problems in the civil-law relations does the application of the institution of transmission easement by adverse possession entail? On account of the functioning of various institutions of easement, that is (1) an easement appurtenant, (2) an easement appurtenant with the content corresponding to a transmission easement, and as of 2008 (3) a transmission easement, a problem arose as to which of the given easements companies exercised in particular periods, all the more so because before 1989 the State Treasury owned them and many of the transmission facilities were put in place by virtue of administrative decisions. The commonly held belief is that in the period of “society-oriented economy” as well as up to 2008 infrastructure companies could exercise an easement appurtenant which corresponded to the content of a transmission easement. Therefore, in such a case the running of the prescriptive period should allow for the general rules laid down for an easement appurtenant. Apart from the problem of the relation of a capacity to exercise a right to property and the free development of civil-law relations before 1989, the recognition of the running of prescriptive periods – given the functioning of the three various easements as legal institutions – became a significant legal problem. By way of illustration, the recognition – against the period of exercising transmission easement – of the period required for the acquisition thereof by adverse possession, whereby before 3 August 2008 the real estate featured the legal state corresponding to the content of this right, is debatable. One cannot recognise that within that period a transmission easement was exercised, because such a right was not in existence as yet. Therefore, the institution that might be employed is the running of the period as regards the adverse possession in relation to an easement appurtenant with the content of a transmission easement. Still, the problem remains as to whether the period of the exercise of the easement appurtenant with the content corresponding to a transmission easement can be recognised against the period of possession required for the adverse possession of a transmission easement pursuant to the regulations introduced in 2008. One might incline to the position whereby in such a case it would be right to fully recognise – against the period of exercising a transmission easement – the period of exercising an easement appurtenant corresponding thereto in respect of its content. That being so, the adverse possession of a transmission easement might ensue in such a situation on 3 August 2008 at the earliest, that is the moment the regulations governing this right come into effect. Conversely, if the prescriptive period expires before that date, the entrepreneur would acquire an easement appurtenant with the content corresponding to the transmission easement. Such an interpretation is aligned with the purpose intended by the legislator, which is to bring order to the actual state of the broadest scope with the aid of a new legal instrument. The text, while analysing the issue of a transmission easement and an adverse possession thereof as a institution of the civil law, presents only some selected problems. Hence, the analysis does not include, for example, the issues concerned with claims for remuneration (for usufruct without contractual basis or usufruct fees), or claims for compensation (redress or amends). Furthermore, the text does not conduct a more profound analysis of the relation between the provisions regulating public-law relations (e.g. acts of law introducing the institution of dispossession) and the provisions regulating civil-law relations (the easements in question).
Keywords: prawo ciwilne; civil law; służebność; easement; służebność przesyłu; transmission easement; ustanowienie służebności przesyłu; establishment of transmission easement; zasiedzenie służebności przesyłu; adverse possession of transmission easement